Review and analysis of the state of the art of studies and management plans carried out in different coastal areas within the framework of coastal risk assessment - Haspert, Federico (2018)
Fil: Haspert, Federico. Ministerio de Obras Públicas. Secretaría de Infraestructura y Política Hídrica. Instituto Nacional del Agua. Subgerencia Laboratorio de Hidráulica; Argentina.